2020
DOI: 10.1007/s12105-019-01123-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral Verruciform Xanthoma: A Series of 212 Cases and Review of the Literature

Abstract: Verruciform xanthoma (VX) of the oral cavity is an uncommon, reactive lesion of unknown etiology. In this study, we present a large series of VX with analysis of demographics, clinical appearance, histologic presentation and extensive review of literature. To the best of our knowledge, this is the largest series of oral VX reported to date. Following IRB approval, all cases diagnosed as VX found in the archives of the University of Florida Oral Pathology Biopsy Service were included. Patient age, gender, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 32 publications
(36 reference statements)
0
33
0
3
Order By: Relevance
“…Ide et al (2008) suggested periodontal pathogens, mechanical stimuli, smoking, alcohol, drugs, and sensitizing or allergic agents of foodstuffs and dental materials are involved in OVX [23]. Belknap et al (2020) noted subepithelial inflammation, which supports the hypothesis that inflammation is the main etiology of OVX [24]. Moreover, de Andrade et al (2015) concluded that inflammation plays a role in the development of OVX [15].…”
Section: Discussionmentioning
confidence: 82%
“…Ide et al (2008) suggested periodontal pathogens, mechanical stimuli, smoking, alcohol, drugs, and sensitizing or allergic agents of foodstuffs and dental materials are involved in OVX [23]. Belknap et al (2020) noted subepithelial inflammation, which supports the hypothesis that inflammation is the main etiology of OVX [24]. Moreover, de Andrade et al (2015) concluded that inflammation plays a role in the development of OVX [15].…”
Section: Discussionmentioning
confidence: 82%
“…First described in 1971 by Shafer, 1 verruciform xanthoma (VX) is a papillary lesion primarily found in the oral mucosa. 2,3 With a proposed incidence rate of oral VX of 0.025%-0.05%, extraoral cases of VX are exceedingly rare, primarily occurring on the skin and anogenital regions, and often found in association with other conditions such as lymphedema and congenital hemidysplasia with ichthyosiform erythroderma and limb defects (CHILD) syndrome. 2,3 The etiology of VX remains unclear, and the lesions have been hypothesized to result from a variety of different mechanisms, including trauma, inflammation, candida infection, carcinoma in situ, and immunologic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 With a proposed incidence rate of oral VX of 0.025%-0.05%, extraoral cases of VX are exceedingly rare, primarily occurring on the skin and anogenital regions, and often found in association with other conditions such as lymphedema and congenital hemidysplasia with ichthyosiform erythroderma and limb defects (CHILD) syndrome. 2,3 The etiology of VX remains unclear, and the lesions have been hypothesized to result from a variety of different mechanisms, including trauma, inflammation, candida infection, carcinoma in situ, and immunologic dysfunction. 2 Oral verruciform xanthoma typically presents as an asymptomatic 2-mm papule to 1.5-cm nodule with a papillary surface, ranging in color from white, red, or yellow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Verruciform xanthoma (VX) is a benign squamous proliferation that presents clinically as a well-circumscribed white, yellow or erythematous papule or plaque with a verrucous surface and a flat or pedunculated base. 3,4 Lesions arising in the oral cavity are most common, and have been described in significant numbers in some series. 4,5 However, an infrequent subset arises at cutaneous sites, 6 often involving the genitals, 7 where they can pose diagnostic challenges clinically as well as histopathologically.…”
Section: Discussionmentioning
confidence: 99%